Padrões setoriais de inovação na indústria brasileira em 2000 - Campos, Bruno Cesar (2005)
The present dissertation investigates features of the technical change in Brazilian industry in 2000 according to the sectoral patterns of innovation literature. The investigation of particularities in innovative conducts of each sector contributes to the comprehension of the rhythm and the direction of technological change. The work utilizes as empirical data the Industrial Survey of Technological Innovation (PINTEC 2000) of the Brazilian Geography and Statistics Institute (IBGE). The proposition of a typology in the innovative performance of the sectors applies hierarchical and non-hierarchical clustering analyses. The characteristics studied are: the innovation sources; the relevant knowledge and learning utilized to innovate; the technological trajectories; the innovative outputs; the market structure and sectoral performance. Considering some exceptions, the results confirm the existence of sectoral patterns of innovation in the Brazilian industry that are similar to other international studies.